A review on finite element analysis of the anterior cruciate ligament reconstruction - Simões; O. J.; Ramos; A.; Oliveira; J. P.; Noronha; J. C.; Simões; J. A (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2021)
A significant number of papers relatively to the investigation made on Anterior Cruciate Ligament (ACL) Reconstruction (ACLR) has been published in orthopaedic related journals. Finite Element (FE) Analysis (FEA) has been used to predict the performance of biomechanical-biomedical systems as well as the effect of clinical factors on the ACLR success. This research tool presents some advantages relatively to experimental studies in assessing stresses and strains in soft tissues of the knee joint. By interpreting correctly FE results, it is possible to extrapolate them to clinical situations. This article reviews papers published from 2016 until nowadays on FEA for ACLR studies searched in Google Scholar, Medline and PubMed databases. Only studies that addressed surgery techniques, type and size of grafts, tunnel geometry and orientation, and fixation devices are reviewed and presented.